Innovations at workplace: an evidence-based model for safety management - Järvis, Marina; Tint, Piia (Business: Theory and Practice, 2009)
Safety culture is a sub-unit of organisational culture, which affects members’ attitudes and behaviour in relation to organisation’s ongoing health and safety performance. Many companies want to enhance their safety culture or some aspect of safety behaviour trying to find the effective way forward. Safety culture in small and medium-scale (SMEs) enterprises has received very little attention in Estonia. Estimates suggest that these enterprises have serious problems aggravated by limited access to human, economic, technological resources as well as lack of relevant occupational health and safety (OH&S) knowledge. The current paper commences with a discussion on the Reciprocal Model of Safety Culture and different perspectives on a framework espoused by Cooper (1999). The concept of safety culture and knowledge management is also discussed. Authors present supplemented Cooper’s Reciprocal Model of Safety Culture with Knowledge Management System Dimensions. The exploratory study based on workplace visits and interviews with owner-managers of SMEs manufacturing enterprises gives an overview of the most characteristic oH&S representations and practices. An overview of the current Estonian OH&S system is also presented based on occupational health (OH) physicians’ questionnaire surveys conducted in 2002 and 2009. The study suggests that there is need for discussion and improvement of collaboration between employers and OH professionals in order to strengthen knowledge management and infrastructure as well as safety culture at the Estonian enterprises. Competence and expertise in work and health topics is the foundation for the added value of OH professionals to the health of working population. Inovacijos darbo vietoje: konstruktyvus darbo saugos vadybos modelis Santrauka. Darbo saugos kultūra yra organizacinės kultūros subvienetas, darantis įtaką organizacijos narių požiūriui ir elgesiui, atsižvelgiant į organizacijoje vykdomą profesinės sveikatos ir darbo saugos politikos lygį. Daugelis kompanijų nori pagerinti saugos kultūrą ar tam tikrą aspektą ir bando rasti efektyvių būdų tam pasiekti. Saugos kultūrai mažose ir vidutinėse įmonėse Estijoje skiriama labai mažai dėmesio. Šios įmonės susiduria su rimtomis problemomis, kurias pagilina ribotas galimybės prieiti prie žmogiškųjų, ekonominių, technologinių išteklių, taip pat žinių trūkumas profesinės sveikatos ir darbo saugos klausimais. Straipsnyje aptariama saugos kultūros ir žinių valdymo koncepcija. Autoriai papildo Cooper (1999) saugos kultūros modelį, įtraukdami ir žinių valdymo sistemos elementus. Remiantis interviu su smulkių ir vidutinių gamybos įmonių vadovais, buvo atliktas tyrimas, kuris atskleidė situaciją, susidariusią profesinės sveikatos ir darbo saugos srityje. Pateikiama Estijos profesinės sveikatos ir darbo saugos sistemos apžvalga, pagrįsta profesinės sveikatos gydytojų anketine apklausa, atlikta 2002–2009 m. Tyrimas parodė, kad reikalingos diskusijos ir bendradarbiavimas tarp darbdavių ir profesinės sveikatos specialistų siekiant pagerinti žinių valdymą bei saugos kultūrą Estijos įmonėse. Reikšminiai žodžiai: žinių vadyba, darbo saugos vadyba, darbo saugos kultūra, darbo aplinka. First published online: 29 May 2009